Mayo Clinic guide to better vision : preventing and treating disease to save your eyesight - Bakri, Sophie J. (Mayo Clinic Press, 2021)
"Having good eyesight is essential for almost every activity we do, but an estimated 93 million adults in the United States are at high risk for serious vision loss. Mayo Clinic Guide to Better Vision is a comprehensive guide to understanding common vision problems, preventing age-related eye disorders, and keeping your eyes healthy at every stage of life"--